STUDENTS’ PERCEPTIONS ON SMALL GROUP DISCUSSION AND WRITING SKILL IN ENGLISH CLASS - Ratnaningsih, Paskalina Widiastuti (Universitas PGRI Palembang, 2025)
This study explores university students' views on using small group discussions to enhance writing skills. Writing is often considered a challenging skill because it requires the ability to organize ideas, construct sentences, and develop coherent paragraphs. Therefore, effective teaching methods are essential to help students improve their writing abilities. The study investigates the role of small group discussions in the writing learning process. Using a survey method, the researchers distributed questionnaires, and the data were analyzed using percentages for each statement. The findings show that students were motivated to learn English writing through small group discussions and that these discussions helped them better understand the writing process. This study contributes to the understanding of how small group discussions can support writing instruction, as previous research has mainly focused on their use in teaching speaking and reading skills.